Line Differential Protection Modeling with Composite Current and Voltage Signal Comparison Method - Hamzah Eteruddin; Abdullah Asuhaimi Mohd Zin; Belyamin Belyamin (Universitas Ahmad Dahlan, 2014)
This paper discusses the protection system which is the most important part in a power system. Increased protection system reliability determines to improve the performance of the entire electrical system. Differential scheme denoted a very reliable method to secure the protection zone. There have been some studies on this topic. However, still need further study in order to obtain a better system, simple and reliable. The resulting model is made in gradually. Each stage is verified to reduce operational errors. Validation was done using the composite method of current and voltage signals, and the sigma delta algorithm as the analog to digital converter. Numerous computing were done to simulate the differential protection system on the underground cable transmission line 420 kV along the 58.5 km, using Matlab / Simulink. The results showed that the proposed method is effective enough to minimize the percentage of errors.